Electrooxidation of methanol on Ag, AgNi, and AgCo catalysts prepared by combustion synthesis technique. (31st October 2022) - Yuda, Afdhal; Kumar, Anand; Abu Reesh, Ibrahim; Russell, Christopher K.; Miller, Jeffrey T.; Ali Saleh Saad, Mohammed; Al‐Marri, Mohammed J.
Summary: Herein, we report the synthesis of silver‐based electrocatalysts (Ag/C, AgCo/C, and AgNi/C) using solution combustion method and their performance towards methanol oxidation reaction. Detailed structural and microscopic analysis confirmed the formation of graphitic carbon, synthesis of crystalline phases with high porosity in all the three electrocatalysts. X‐ray photoelectron spectroscopic (XPS) analysis showed a high concentration of Ag2 O (or Ag + ) on AgNi/C, whereas AgCo/C exhibited a high concentration AgO (or Ag 2+ ) on the surface. XPS analysis on C 1s confirmed the highest concentrations of the sp 2 hybridized CC bond on Ag/C, CO on AgNi/C, and OCO bond on AgCo/C, respectively. The X‐ray absorption spectroscopy (XAS) analysis on Ag edge showed a similarity in the bond lengths in AgCo and AgNi samples to that of bulk silver, that has a bond length of 2.89 Å, with only silver‐silver scattering and the absence of a different or a nonsilver metal in the nanoparticles. This indicates that there is no Ag‐M alloying. Nonetheless, a significant difference in particle sizes was observed, with 2.5 and 6 nm, respectively for AgNi and AgCo. Methanol electrooxidation experiments performed on the electrocatalysts indicated AgNi/C to show better performance in comparison to AgCo/C and Ag/C. Anodic polarization curves obtained from linear sweep voltammetry (LSV) measurements demonstrated a superior performance of AgNi/C with an onset potential of 0.41 V. In addition, 20 h chronoamperometry experiment also confirmed a sustained superior performance of AgNi/C catalyst, which could be due to smaller particle size and stabilization of Ag+ on the surface of the catalyst. Abstract : Three Ag‐M electrocatalysts (Ag/C, AgNi/C and AgCo/C) were synthesized using combustion synthesis method. All the three catalysts showed the presence of graphitic carbon after the synthesis. A detailed structural analysis indicates alloying at the surface of AgNi and AgCo, whereas segregation of bulk phases. AgNi/C showed the best performance for methanol oxidation. Based on XPS analysis, the surface trapped Ag+ stabilized in AgNi could be responsible for better catalytic performance of AgNi/C catalyst.